Tren Penelitian Global tentang ASI Eksklusif: Analisis dan Visualisasi Bibliometrik pada Database Scopus (2021-2024) - Mashadi, Aisya; Hasibuan, Rachma; Riasti, Novida; Nusroh, Khuliyatul; Ikromatus Sa’adah, Izza (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Exclusive breastfeeding during the first six months of life is one of the most effective public health interventions for preventing infant mortality and improving child nutritional status. However, its practice continues to face numerous challenges, including policy constraints, cultural barriers, and limited access to information. This study aims to analyze trends, collaboration patterns, and topical focus in scientific publications on exclusive breastfeeding during the period 2020–2024. The method employed in this study is a quantitative-descriptive approach using bibliometric analysis based on data retrieved from the Scopus database. The collected data were then analyzed using VOSviewer software to identify publication trends, citation patterns, and prevalent keywords. Based on bibliometric analysis and visualization, global research trends on exclusive breastfeeding show a declining pattern during the period from 2020 to 2024, with a peak in publication activity observed in 2020 followed by a decrease in subsequent years. Through analysis using VOSviewer, seven major thematic clusters were identified, featuring dominant keywords such as exclusive breastfeeding, stunting, and infant health. The analysis and visualizations in this study highlight both well-established themes and underexplored areas, including postpartum factors and anthropometric indicators. These findings confirm a shift in research focus and offer direction for future studies and the development of informed policies.